Analisis Faktor-Faktor yang Mempengaruhi Rendahnya Keterlibatan Ibadah di Kalangan Remaja Muslim Usia 15-19 Tahun di Jakarta dan Sekitarnya - Adhha Muzaky Hudzaifah; Rais Kamil Taqiy; Ariq Hammam Abdullah; Yuminah Yuminah (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This study aims to identify and analyze factors influencing the low involvement in religious worship among Muslim adolescents aged 15-19 years in Jakarta and surrounding areas. A qualitative approach was employed using semi-structured in-depth interviews with 20 purposively selected participants. Thematic analysis revealed four main themes: limited and contextually irrelevant religious understanding, peer social pressure, distractions from social media and digital technology, and lack of family support and active role models. These findings provide a basis for developing contextual and interactive religious education programs, enhancing family roles, and utilizing digital media as effective tools for religious motivation. Recommendations are directed to educators, families, and communities to sustainably increase adolescent worship engagement.